Cystatin C versus Creatinine in Determining Risk Based on Kidney Function - Shlipak, Michael G; Matsushita, Kunihiro; Ärnlöv, Johan; Inker, Lesley A; Katz, Ronit; Polkinghorne, Kevan R; Rothenbacher, Dietrich; Sarnak, Mark J; Astor, Brad C; Coresh, Josef; Levey, Andrew S; Gansevoort, Ron T (The New England journal of medicine, 2013)
In this meta-analysis of 16 studies, investigators evaluated the use of cystatin C, alone or with creatinine, to calculate the estimated glomerular filtration rate (eGFR). Measurement of cystatin C improved the prediction of outcomes in chronic kidney disease. The estimated glomerular filtration rate (eGFR) is the clinical standard for the assessment of kidney function. 1 – 3 The eGFR thresholds for the definition and staging of chronic kidney disease are based on risk, 3 but measurement of creatinine to determine the eGFR has limitations in risk prediction, particularly in patients with reduced muscle mass. 4 Cystatin C has received much attention as an alternative filtration marker with stronger and more linear risk relationships than creatinine. 5 – 7 Several studies have suggested that the addition of cystatin C measurements to creatinine measurements in calculating the eGFR significantly improves the risk classification for death, cardiovascular . . .